Gasp. Struggle. Let Go - McCabe, Kate (Art/Research International)

(untitled) (University of Alberta, 2022)
This writing explores what continues to arise after my cancer diagnosis. A cancer diagnosis enlivens the question of what it means to live well with the Earth and its multi-dimensional beings and provides a necessary push to step out from the confines of a self and toward and into the wild fray of this life. I interpret my lived experiences through life writing. Readers and listeners might be drawn into recognition of their inescapable ecological interdependence. The necessity of cultivating an ability to listen and interpret the world and the human and other-than-human kinships becomes undeniable as I engage in life-writing and photography. Listening to words that arise in my writing and reviewing the photos I take continues to be my way of taking a journey toward learning to be open to the fullness of life, how life is lived, how life can be remembered and suffered and let go. Through this study, I am learning the necessary steps to unforget what I need and what the Earth might need of me. Cancer offers an opening for the practice of life-writing and of making sense of being in the world and of understanding the offerings that arrive when I nurture a commitment to care for the world and myself.